Paediatric clinical examination made easy - Gill, Denis; O'Brien, Niall (Niall Gerard) (Elsevier, 2018)
This comprehensive undergraduate medical textbook on the paediatric clinical examination covers not only the medical information, but also advice on dealing with small children, their parents, and breaking bad news